2001
DOI: 10.1074/jbc.m104043200
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibits Methionine Synthase Activity in Vivo and Disrupts Carbon Flow through the Folate Pathway

Abstract: Many of nitric oxide's biological effects are mediated via NO binding to the iron in heme-containing proteins. Cobalamin (vitamin B 12 ) is structurally similar to heme and is a cofactor for methionine synthase, a key enzyme in folate metabolism. NO inhibits methionine synthase activity in vitro, but data concerning NO binding to cobalamin are controversial. We now show spectroscopically that NO reacts with all three valency states of cobalamin and that NO's inhibition of methionine synthase activity most like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 39 publications
4
94
0
3
Order By: Relevance
“…This conclusion is corroborated by a recent report suggesting that NO inhibits the MS reaction, thereby blocking the flow of one carbon units through the folate pathway. 4 Our results and this report prompted us to examine the possibility that NO induction of NTD is caused by inhibition of the MS reaction. To this end, eight somite stage embryos were treated with 2 mM SNAP in the presence or absence of FA.…”
Section: Dear Editormentioning
confidence: 88%
See 2 more Smart Citations
“…This conclusion is corroborated by a recent report suggesting that NO inhibits the MS reaction, thereby blocking the flow of one carbon units through the folate pathway. 4 Our results and this report prompted us to examine the possibility that NO induction of NTD is caused by inhibition of the MS reaction. To this end, eight somite stage embryos were treated with 2 mM SNAP in the presence or absence of FA.…”
Section: Dear Editormentioning
confidence: 88%
“…Nitric oxide (NO) had been shown to be able to induce NTD in 10.5-day rat embryos, 3 and biochemical studies showed that NO inhibits methionine synthase (MS), by interfering with the transfer of the methyl group from the methyl donor 5-methyl-tetrahydrofolate (5mTHF) to homocysteine. 4 We have shown that endogenously produced NO in the neuroepithelium, at the time of NT closure, plays a role in cell cycle progression 5 and the regulation of cell numbers in the developing NT. 6 We also found that high NO levels increase the demand for folates.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The present studies demonstrated an ethanol-induced inhibition of MS activity that could explain the reduced liver methionine and SAM levels (Tables 1 and 2). Others showed that nitric oxide inactivates MS (60) because of interaction with its cobalamin cofactor (61). MAT activity is reduced posttranslationally through nitrosylation of cysteine residue 121 in MATI͞III (62), whereas its activity is maintained in part by GSH (63).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, direct loss of vitamins and mineral trace elements from the organism of the animals can occur during exposure to an external stress (such as for example, a climatic stress), since MS-Co(II), an inactivated form of vitamin B12 produced by oxidation of MS-Co(I) in the course of enzymatic methionine synthesis, can be oxidized by ROS [110,115]. Indeed, inactivation of vitamin B12 by • NO [115] has been reported and is involved in pernicious anemia in humans, after disturbing both methionine synthesis and carbon flow through the folate pathway [116].…”
Section: Defense Against Ros and The Outcome Of Gestationmentioning
confidence: 99%